Inclusive, transformative agri-food systems for sustainable healthy diets, better nutrition, and health - Blare, Trent; Bliznashka, Lilia; Chavarro, Monica Juliana; Jaleta, M.; Kasala, Kavitha; Lopez-Avila, Diana; Ravula, Padmaja (2025)
Considerable progress has been made on nutrition research that informs efforts to enhance food and nutrition security of the most vulnerable and socially excluded populations. Yet, gaps remain in ensuring that all have healthy diets that promote growth; physical, social, and emotional development; and wellbeing, while preventing nutrient deficiencies and non-communicable diseases (NCDs) [1]. While undernutrition remains a critical concern, NCDs like hypertension, type 2 diabetes, and obesity are becoming more prevalent globally. Additionally, food production challenges such as the aging and outmigration of farmers, climate change and variability, and the limited adoption of sustainable production practices hinders the ability to source a diverse, sustainable, and nutritious diet. These challenges are exacerbated by neglecting gender equality and social inclusion (GESI) [2,3]. Women, youth, and socially excluded groups — such as indigenous communities, displaced populations or people with disabilities — face additional barriers to achieving food and nutrition security, including restricted access to resources, limited decision-making power, and reduced economic opportunities. To achieve greater impact, research and implementation efforts must prioritize gender and social inclusion by addressing the specific challenges faced by women, youth, the poor, and other socially excluded groups, requiring a thorough understanding of their unique obstacles and the compounded consequences from belonging to multiple socially excluded groups. The need to address undernutrition and basic food security continues to be one of the main priorities for research. Child stunting and wasting, and women’s underweight and micronutrient deficiencies are persistent problems globally [4]. Additionally, the prevalence of overnutrition and NCDs is increasing, with unhealthy diets among the primary risk factors [5]. Industrialized agri-food systems are a key driver of these negative health outcomes. Overconsumption of ultra processed foods along with micronutrient deficiencies contribute to rising rates of NCDs while failing to alleviate undernutrition [6]. Problems with water availability, accessibility, and quality negatively impact agri-food systems and contribute to poor health, nutrition, and well-being [7]. The simultaneous manifestation of undernutrition and overnutrition is the double burden of malnutrition and can manifest at the individual, household, or country level [8]. Triple burden of malnutrition can also occur in individuals or households as underweight, micronutrient deficiencies, overweight/obesity, or NCDs [9].